On the Refinement of Compensation-Based Semantics for Weighted Argumentation Frameworks - Viana, Henrique; Alcântara, João (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2021)
Acceptability semantics for the frameworks of weighted argumentation can satisfy up to one of the principles of (Quality Precedence), (Cardinality Precedence) or (Compensation), which are pairwise incompatible. In this paper we define two new principles: (Quality Compensation) and (Cardinality Compensation), which are weakened versions of (Quality Precedence) and (Cardinality Precedence), respectively. We show that these new principles are compatible with (Compensation) and propose two new semantics: a t-conorm-based, which can satisfy (Quality Compensation) and a cumulative sum-based semantics, which satisfies (Cardinality Compensation).